TRANSPARENCY AND ACCOUNTABILITY OF SCHOOL OPERATIONAL ASSISTANCE fUNDS AND THE IMPACT ON PARTICIPATION - Dita Puruwita (Econosains Jurnal Online Ekonomi dan Pendidikan, 2018)
The research aims to obtain valid, factual information and knowledge about how the influence between transparency and accountability towards participation in Vocational School in Jakarta, Indonesia. The population of this research is the principal, teachers, student's parents. The technical analysis used is multiple linear regression analysis. The findings of this study are: 1) there is a positive effect between transparency and the participation of students' parents. 2) There is a positive effect between accountability with the participation of student's parents and 3) there is a positive effect between transparency and accountability towards the participation of student's parents.